'International Community' as a Legal Notion - Christian J. Tams (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2018)
The 'international community' is omnipresent in international debates. It is a point of reference. Much international action is undertaken in its name. And many a catastrophe – from Aleppo to climate change – is portrayed as a failure of the international community. As is clear from these random references, the functions, meanings and content of the concept of 'international community' are fluid: it is as appealing as it is evasive – and in fact, often it appeals precisely because it is evasive, and because a wide range of diverse, sometimes competing, meanings and expectations are projected onto it. The working paper seeks to unveil some of the functions, meanings and expectations projected upon the notion of 'international community'. While it focuses on debates in one particular field, viz. international law, its themes are of significance to a wider audience.
urn:nbn:de:hbz:464-20190219-174931-5
Keywords: 320; international community; international law; society; United Nations; law-making